Seasonal pattern of lesion development in diseased Fraxinus excelsior infected by Hymenoscyphus pseudoalbidus. - Stina Barbro Katrin Bengtsson; Pia Barklund; Claudia von Brömssen; Jan Stenlid (PLoS ONE)
Ash dieback is a recent widespread disease on ash (Fraxinus sp.) that is causing important economic and ecological losses throughout Europe. The disease is initiated by the ascomycetous fungus Hymenoscyphus pseudoalbidus (anamorph Chalara fraxinea). The main aim of this study was to investigate seasonal pattern of lesion development associated with ash dieback. We present data on the spread of 324 natural lesions in ash shoots, branches and stems surveyed over a 32 month period. Most lesions were active and showed the greatest rate of growth during the summer; however, lesions were active throughout the year. Tree mortality was high, with more than a third of the surveyed trees dying during the study. Although many lesions permanently ceased to develop, the rate at which new lesions emerged was greater than the rate at which lesions entered a resting phase. The most common cause for a lesion going into a permanent state of rest was that it had encountered a branch-base. Genotype analysis showed that multiple infections can occur in a single tree given that different genotypes were identified in different lesions as well as in single lesions. A weak positive correlation was noted between tree health and tree size and a weak negative correlation was noted between tree overall health and lesion activity. The lower limit for H. pseudoalbidus growth in culture was between 4.0°C and 0.5°C.